A Multidimensional Version of Levin’s Secular Constant Theorem and its Applications - Favorov, S. Yu.; Girya, N. (Журнал математичної фізики, аналізу, геометрії, 2007)
We study holomorphic almost periodic functions on a tube domain with the spectrum in a cone. We extend to this case Levin’s theorem on a connection between the Jessen function, secular constant, and the Phragmen-Lindelöf indicator. Then we obtain a multidimensional version of Picard’s theorem on exceptional values for our class.Mathematics Subject Classification: 42A75, 30B50.